Search for t(t)over-bar resonances in highly boosted lepton plus jets and fully hadronic final states in proton-proton collisions at root s=13 TeV - Sirunyan,AM; Tumasyan,A; Adam,W; Asilar,E; Bergauer,T; Brandstetter,J; Brondolin,E; Dragicevic,M; Eroe,J; Flechl,M; Friedl,M; Fruehwirth,R; et al. (Journal of High Energy Physics, 2017)
A search for the production of heavy resonances decaying into top quark-antiquark pairs is presented. The analysis is performed in the lepton+jets and fully hadronic channels using data collected in proton-proton collisions at s√=13s=13 TeV using the CMS detector at the LHC, corresponding to an integrated luminosity of 2.6 fb−1. The selection is optimized for massive resonances, where the top quarks have large Lorentz boosts. No evidence for resonant tt¯tt¯ production is found in the data, and upper limits on the production cross section of heavy resonances are set. The exclusion limits for resonances with masses above 2 TeV are significantly improved compared to those of previous analyses at s√=8s=8 TeV.